2021
DOI: 10.3390/ijms22020821
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in the Ability to Release Neutrophil ExtraCellular Traps in the Course of Childhood Acute Leukemias

Abstract: Acute leukemias, the most common cancers in children, are characterized by excessive proliferation of malignant progenitor cells. As a consequence of impaired blood cell production, leukemia patients are susceptible to infectious complications—a major cause of non-relapse mortality. Neutrophil extracellular traps (NETs) are involved in various pathologies, from autoimmunity to cancer. Although aberrant NETs formation may be partially responsible for immune defects observed in acute leukemia, still little is kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Immunofluorescence and flow cytometry showed that ETosis abilities of immature neutrophils were impaired in APL, while ETs secreted by mature neutrophils increased. Magdalena Ostafin reported that immature neutrophils isolated from AML are characterized by a low ability to secrete ETs, which is in accordance with our findings ( 33 ). It is postulated that the insignificant trend of elevated ETs in ND APL patients is due to the high content of promyelocytes.…”
Section: Discussionsupporting
confidence: 92%
“…Immunofluorescence and flow cytometry showed that ETosis abilities of immature neutrophils were impaired in APL, while ETs secreted by mature neutrophils increased. Magdalena Ostafin reported that immature neutrophils isolated from AML are characterized by a low ability to secrete ETs, which is in accordance with our findings ( 33 ). It is postulated that the insignificant trend of elevated ETs in ND APL patients is due to the high content of promyelocytes.…”
Section: Discussionsupporting
confidence: 92%
“…The structure of NETs formed by granule proteins and DNA induces the proliferation of cancer cells through high mobility group protein B1 (HMGB1) and NE [ 46 48 ]. In hematological malignancies, levels of NETs are found to positively correlated with lymphoma progression or childhood acute leukemia development [ 49 , 50 ].…”
Section: Neutrophils In Cancer Progressionmentioning
confidence: 99%
“…Inhibition of the key modulation factor of the B cell receptor signaling pathway have been proven to be an effective therapeutic approach for AML ( 63 ). In addition, NET has been implicated in a variety of pathologies from autoimmunity to cancer, and its release was impaired in AML ( 64 ). It may contribute to the increased susceptibility of this population ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NET has been implicated in a variety of pathologies from autoimmunity to cancer, and its release was impaired in AML ( 64 ). It may contribute to the increased susceptibility of this population ( 64 ). CAR-T cell therapy has been used for the treatment of AML ( 65 ), which induces T cell activation, proliferation, and effector function through the binding of reprogrammed T cells to relevant antigens on the surface of tumor cells, ultimately leading to tumor cell death ( 66 ).…”
Section: Discussionmentioning
confidence: 99%